The nuclear import of Frizzled2-C by Importins-beta11 and alpha2 promotes postsynaptic development. - Mosca, T.J.; Schwarz, T.L. (Nature Neuroscience, 2010)
Synapse-to-nucleus signaling is critical for synaptic development and plasticity. In Drosophila, the ligand Wingless causes the C terminus of its Frizzled2 receptor (Fz2-C) to be cleaved and translocated from the postsynaptic density to nuclei. The mechanism of nuclear import is unknown and the developmental consequences of this translocation are uncertain. We found that Fz2-C localization to muscle nuclei required the nuclear import factors Importin-beta11 and Importin-alpha2 and that this pathway promoted the postsynaptic development of the subsynaptic reticulum (SSR), an elaboration of the postsynaptic plasma membrane. importin-beta11 (imp-beta11) and dfz2 mutants had less SSR, and some boutons lacked the postsynaptic marker Discs Large. These developmental defects in imp-beta11 mutants could be overcome by expression of Fz2-C fused to a nuclear localization sequence that can bypass Importin-beta11. Thus, Wnt-activated growth of the postsynaptic membrane is mediated by the synapse-to-nucleus translocation and active nuclear import of Fz2-C via a selective Importin-beta11/alpha2 pathway.